Race modifies survival benefit of guideline‐based treatment: Implications for reducing disparities in muscle invasive bladder cancer - Samuel L. Washington III; Steven E. Gregorich; Maxwell V. Meng; Anne M. Suskind; Sima P. Porten (Cancer Medicine, 2020)
Abstract Background Black individuals with muscle‐invasive bladder cancer (MIBC) experienced 21% lower odds of guideline‐based treatment (GBT) and differences in treatment explain 35% of observed Black‐White differences in survival. Yet little is known of how interactions between race/ethnicity and receipt of GBT drive within‐ and between‐race survival differences. Methods Black, White, and Latino individuals diagnosed with nonmetastatic, locally advanced MIBC from 2004 to 2013 within the National Cancer Database were included. Guideline‐based treatment was defined as the receipt including one or more of the following treatment modalities: radical cystectomy (RC), neoadjuvant chemotherapy with RC, RC with adjuvant chemotherapy, and/or chemoradiation based on American Urological Association guidelines. Cox proportional hazards model of mortality estimated effects of GBT status, race/ethnicity, and the GBT‐by‐race/ethnicity interaction, adjusting for covariates. Results Of the 54 910 MIBC individuals with 125 821 person‐years of posttreatment observation (max = 11 years), 6.9% were Black, and 3.0% were Latino. Overall, 51.4%, 45.3%, and 48.5% of White, Black, and Latino individuals received GBT. Latino individuals had lower hazard of death compared to Black (HR 0.81, 95% CI 0.75‐0.87) and White individuals (HR 0.92, 95% 0.86‐0.98). With GBT, Latino and White individuals had similar outcomes (HR = 1.00, 95% 0.91‐1.10) and both fared better than Black individuals (HR = 0.88, 95% 0.79‐0.99 and HR = 0.88, 95% 0.83‐0.94, respectively). Without GBT, Latino individuals fared better than White (HR = 0.85, 95% 0.77‐0.93) and Black individuals (HR = 0.74, 95% 0.67‐0.82) while White individuals fared better than Black individuals (HR = 0.87, 95% 0.83‐0.92). Black individuals with GBT fared worse than Latinos without GBT (HR = 1.02, 95% 0.92‐1.14), although not statistically significant. Conclusion Low GBT levels demonstrated an “under‐allocation” of GBT to those who needed it most—Black individuals. Interventions to improve GBT allocation may mitigate race‐based survival differences observed in MIBC.